Brian Pena Garcia: capstone - Pena Garcia, Brian, artist (Colorado State University. Libraries, 2023)
The artist's statement: As a Mexican immigrant I've had to witness and experience a lot of mistreatment while living in the U.S. Feeling the pressure of being the absolute perfect model citizen in a country that doesn't respect or care for my existence is exhausting. With no financial sustainability or support medically, I've seen my family and other immigrants struggling year after year. Even though Undocumented Immigrants pay Billions of dollars in taxes every year, we are still not accepted as citizens. For my project I would like to explore the feelings and sentiments I have felt through my life in growing up in the U.S. as a Mexican immigrant. Throughout my years of watching the political climate in constant fear, to my personal experience of racial discrimination, I want to create illustrations in ink that demonstrate the aspects of being an immigrant in the United States. Some examples of concepts I'd like to explore are the experiences in the work environment. Being underpaid, working more hours, and having no choice in where to work are a few points that describe the situation of work for undocumented immigrants. Another aspect is the ability to see family from their home country. Undocumented immigrants usually don't have the money to travel, and if they did it would be impossible to leave the U.S. because they would no longer be able to come back. This causes them to not be able to see their family. This is an experience I had to go through in my family and witness this pain in my parents. Pieces like "Thinking of Mexico" explore this feeling of diaspora that Mexican immigrants deal with when it comes to being in the United States. Only experience my birthplace through memories while experiencing the unjust systematic discrimination and oppression in the U.S.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing